2004
DOI: 10.1111/j.0908-8857.2004.03146.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg characteristics are unreliable in determining maternity in communal clutches of guira cuckoos Guira guira

Abstract: Egg characteristics have been used to determine egg maternity for birds in situations where two or more females lay eggs in a single nest (as in communal breeders and intraspecific parasites). We assessed the applicability of egg morphometry and eggshell appearance in ascribing egg ownership in communal clutches of guira cuckoos Guira guira, a species where up to seven females may lay eggs in a joint nest. We used both combined variables (including egg mass, length, width, shape and two eggshell variables), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…To summarize, we offer genetic evidence that a case of super‐normal clutch size in the northern lapwing did not involve IBP. Further, the absence of IBP in a nest with varying egg morphology supports the findings of other authors (McRae 1997, Ådahl et al 2004, Cariello et al 2004). These results suggest that classifying IBP based on egg characteristics is too tentative and that IBP should be genetically analysed.…”
Section: Band‐sharing Values From Multi‐locus Dna Fingerprinting For supporting
confidence: 90%
See 1 more Smart Citation
“…To summarize, we offer genetic evidence that a case of super‐normal clutch size in the northern lapwing did not involve IBP. Further, the absence of IBP in a nest with varying egg morphology supports the findings of other authors (McRae 1997, Ådahl et al 2004, Cariello et al 2004). These results suggest that classifying IBP based on egg characteristics is too tentative and that IBP should be genetically analysed.…”
Section: Band‐sharing Values From Multi‐locus Dna Fingerprinting For supporting
confidence: 90%
“…We have not found other studies that have used molecular evidence to analyse if egg characteristics predicts intra‐specific brood parasitism (IBP) in shorebirds, but it has been done in the moorhen Gallinula chloropus (egg size, egg coloration, and interval between appearance of eggs; McRae 1997) and in the guira cuckoo Guira guira (egg size and colouration; Cariello et al 2004). These studies found that IBP could not be reliably determined based on egg size or egg colouration.…”
Section: Band‐sharing Values From Multi‐locus Dna Fingerprinting For mentioning
confidence: 99%
“…Three of the four species have been subjects of long-term behavioral studies: Groove-billed Ani (Crotophaga sulcirostris) in Costa Rica (Vehrencamp 1977(Vehrencamp , 1978Vehrencamp et al 1986;Koford et al 1990); Smooth-billed Ani (C. ani) in Florida and Puerto Rico (Davis 1940, Loflin 1983, Quinn and Startek-Foote 2000, Schmaltz et al 2008; and Guira Cuckoo (Guira guira) in Brazil (Macedo 1992;Cariello et al 2002Cariello et al , 2004Macedo et al 2004). Several individuals (both males and females) in all three species cooperate to build a single nest in which all of the females lay their eggs.…”
mentioning
confidence: 99%
“…In addition to the Common Goldeneye, studies of the Ring-billed Gull (Larus delawarensis; Fetterolf and Blokpoel 1984) Cariello et al 2004), however, have found the opposite, that egg morphology is unreliable for the detection of nest parasitism. Therefore, evaluation of morphology-based methods appears to be necessary on a case-by-case basis for each species.…”
Section: Egg Morphology Is An Unreliable Indicator Of Intraspecific Nmentioning
confidence: 99%